Effects of acute endurance exercise on gene expression in skeletal muscle: Search for putative myokines - Catoire, M.; Mensink, M.; Boekschoten, M. V.; Müller, M.; Schrauwen, P.; Kersten, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Exercise is known to be a powerful way to prevent and treat type 2 diabetes mellitus. Skeletal muscle is the predominant organ impacted by exercise but many of the metabolic changes induced by exercise may involve the liver. An important question is how exercise- or better skeletal muscle contraction - can alter hepatic function and insulin action. It is hypothesized that myokines play an important role in the cross-talk between skeletal muscle and liver. Since only a few myokines are known so far, identifying unknown myokines might provide valuable information for future research on the pathogenesis and treatment of type 2 diabetes mellitus. The aim of this study was to investigate the effect of acute endurance exercise on gene expression in skeletal muscle, with a focus on potential myokines, and to assess the importance of local and systemic effects of exercise on gene expression in skeletal muscle. Methods: Nine healthy, male subjects (40-60 years) cycled for one hour with one leg at a submaximal rate. The passive leg served as control. Before and after exercising, muscle biopsies were taken from both legs and analyzed with microarray to determine which genes changed in response to exercise. Results: One-legged cycling induced a significant change in 761 genes (p<0.01), of which 594 were significantly upregulated and 167 genes were downregulated. In contrast, in the control leg only 235 genes changed significantly (p <0.01; 165 upregulated, 70 downregulated). There was an overlap of 63 genes between both legs. In the exercising leg the top 3 regulated genes all belonged to the NR4A transcription factor family, with a highest fold change of 25 (NR4A2). In the non-exercising leg the top 3 consisted of ANGPTL4, PDK4 and ZNF750, with the highest fold change of 2.1 for ANGPTL4. Genes coding for potentially secreted proteins were (amongst others): ANGPTL4, THBS1 (both legs), CYR61, MCP-1, VEGFA and CX3CL1 (exercising leg). Conclusion: Exercise-induced gene expression changes are the result of both systemic and local stimuli. The NR4A transcription factor family are potential regulators of the adaptive processes that take place in skeletal muscle during and after exercise. Several putative myokines are identified that are involved in processes such as angiogenesis, growth, insulin signaling and lipid metabolism.